Evaluation of La sub(0.4)Ba sub(0.6)Fe sub(0.8)Zn sub(0.2)O sub(3- delta ) + Sm sub(0.2)Ce sub(0.8)O sub(1.9) as a potential cobalt-free composite cathode for intermediate temperature solid oxide fuel cells - Bu, Yun-fei; Ding, Dong; Lai, Samson Yuxiu; Chen, Dong-Chang; Xiong, Xun-Hui; Wei, Tao; Zhong, Qin (Journal of power sources, 2015)
The disadvantages of cobalt-based and barium-based perovskite oxides in solid oxide fuel cells are the large thermal expansion coefficients, low structure stability, and poor CO sub(2) tolerance, although they have excellent oxygen reduction activity. To reduce the impact of these detrimental effects, cobalt-free La sub(0.4)Ba sub(0.6)Fe sub(0.8)Zn sub(0.2)O sub(3- delta ) (LBFZ) was investigated as a potentially promising cathode material for intermediate temperature solid oxide fuel cells (IT-SOFCs). The TEC of LBFZ is 18.9 x 10 super(-6) K super(-1), which is lower than other widely used cobalt-containing cathode materials. The electrode performance can be further improved by incorporating Ce sub(0.8)Sm sub(0.2)O sub(1.9) (SDC) to form a composite. Systematic study suggests that composite cathodes containing 40 wt% SDC exhibited the best electrode performance (R sub(p) = 0.12 [Omega] cm super(2)) when they were fired at 1050 [degrees]C for 2 h, correlating to a peak power density of 839 mW cm super(-2) based on the single cell with the configuration NiO-YSZ/YSZ/SDC/LBFZ-SDC at 700 [degrees]C. Also, LBFZ-SDC demonstrated excellent chemical stability upon exposure to 1% CO sub(2) at 550 [degrees]C for 100 h, and the electrochemical testing also demonstrated better CO sub(2) tolerance than Ba sub(0.5)Sr sub(0.5)Co sub(0.8)Fe sub(0.2)O sub(3- delta ) (BSCF). These results suggest that LBFZ and its SDC composite are promising cathode materials for IT-SOFCs.